2009
DOI: 10.2139/ssrn.1340210
|View full text |Cite
|
Sign up to set email alerts
|

How Do Public Laboratories Collaborate with Industry? New Survey Evidence from France

Abstract: This paper uses a survey of 130 public laboratories in France to investigate collaborative activities of laboratories with industry. Our statistical analysis shows that knowledge and technology development and transfer occurs most frequently through collaborative and contract research, informal exchanges, conferences, and consortia. The main benefits from the perspective of laboratories are the tangible and intangible inputs received-funds, materials, research suggestions and data. The outputs of collaboration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In particular, when firms collaborate with universities or governmental research institutes, publication is likely. Goddard and Isabelle (2006) indicate, for example, that co‐publications are the most frequently occurring outcome of research collaboration between French academic organisations and firms.…”
mentioning
confidence: 99%
“…In particular, when firms collaborate with universities or governmental research institutes, publication is likely. Goddard and Isabelle (2006) indicate, for example, that co‐publications are the most frequently occurring outcome of research collaboration between French academic organisations and firms.…”
mentioning
confidence: 99%
“…Another study covering 194 SMSAs in the USA found a positive correlation between the amount of R&D expenditures in the private sector and in the public science institutions (Bania et al, 1992). European studies with a similar research design (Goddard and Isabelle, 2006; come to comparable findings.…”
Section: Knowledge Spill-overs In Empirical Research: Operationalisatmentioning
confidence: 86%
“…; von Proff and Dettmann ). Studies that use survey data to capture the geographical determinants of university‐industry collaboration, although they explore the characteristics of the interactions in more detail, do not investigate the objectives of collaboration (Goddard and Isabelle ; D'Este and Patel ; Garcia‐Aracil and Fernandez De Lucio ; Bruneel et al. ).…”
Section: Regional University‐industry Collaboration: Channels and Objmentioning
confidence: 99%